PALM KERNEL SHELL BIOCHAR CATALYST FOR BIODIESEL PRODUCTION FROM WASTE COOKING OIL. Issue 1 (February 2021) - Widayat,; Fernanda, A A A; Silvie, E S
Abstract: Biodiesel is an alternative fuel and have properties similar to conventional diesel. The process of making biodiesel requires two stages of the process, namely esterification then proceed with the transesterification. But to keep the process efficient, the esterification and transesterification are carried out simultaneously. A new type of catalyst is being developed that comes from carbonization of incomplete natural products called biochar. Biochar has better catalyst performance for FFA esterification, and higher stability than other solid acid catalysts. The research procedure consist of stages: Pretreatment Palm Kernel Shell (PKS), Increasing Surface Size and Porosity, catalyst impregnation with H2 SO4 and (NH4 )2 Fe(SO4 )2 .6H2 O, and the biodiesel manufacture. Weight variations of the catalyst (1% wt; 1.5 wt%; 2% wt, 2.5% wt; and 3% wt) and variations of temperature (50°C; 55°C; 60°C; 65°C; 65°C and 70°C ) to the %FAME biodiesel produced, is used in this research .